Does Instagram’s Like Affected Teenager Self- Worth? - Ipmawati, Hayinah; Pratisti, Wiwien Dinar (International Journal of Psychosocial Rehabilitation, 2020)
This literature review was conducted to identify that instagram’s like affected teenager self- worth. We know that instagram has become a phenomenal social platform with 800 million user around the world. While, Indonesia has become the big 3 instagram’s user, after America and Brazil with about 60 million user. Instagram was super phenomenal among teenager, like every teenager are active instagram users, and while teenage is an age to search identity, so it’s so much important to know that teenage self is worth it. Well we know that instagram provides picture, followers, comments, likes, direct message etc. which make people get in touch easily with other people, building a good relationship, make us feel happy while receiving likes, comments and other responses from others. Besides that, there are a pressure for someone to get likes, some comments and followers that can produce a high anxiety, social pressure and it can make our self-feel unworthy. These phenomena correlated with a part of self esteem, called self-worth. Self-worth is how someone see their own value or worth as a person. While knowing source of self-worth, achieve something, approval and acceptance from others, virtue or one’s judgment of moral adequacy are sources of self-worth which can easily gained by instagram’s like, means that we can also get self-worth by instagram’s like. The result of this study found that, instagram’s like is affected self-worth.